Product Bundling and Shopping Cart Value of Home Snack MSMEs in Social Commerce: A Review of the Literature - Ninik Nurhayati (International Journal of Economics Business and Social Sciences, 2026)
The growth of social commerce makes home snack MSMEs need to organize offers that not only attract attention, but also be able to encourage an increase in the value of shopping carts in the transaction process which is greatly influenced by content and interaction. This article is compiled to summarize and synthesize the literature on product bundling and the mechanisms that explain its relationship with shopping cart value in the context of social commerce. Literature searches were conducted through the National Library, Google Scholar, and ScienceDirect with keywords related to bundling, shopping cart value, live shopping, perceived value, and impulse purchases. The selection of sources is carried out in stages through the study of titles, abstracts, and full texts with publication limits for 2021-2025, in the form of relevant journals and books and the contents can be traced. The collected data is compiled into a matrix containing definitions, indicators, contexts, approaches, and key findings, then analyzed using a thematic-comparative synthesis. The results of the study show that bundling functions as an offering design that strengthens perceived value and simplifies consumer choice; The live shopping environment features the roles of social presence, trust, and flow related to impulse buying; and there is a difference in research outputs between purchase intention and the size or value of the shopping cart. This article confirms that bundling has the opportunity to help increase the value of the shopping basket when positioned as a value booster in the social shopping experience. The implication is that MSMEs need to maintain clarity of package value, suitability of composition, and consistency of promotional messages, so that bundling not only looks more economical, but is also easy to choose and really felt useful by consumers.